Insight into the role of microbial calcium carbonate and the factors involved in self-healing concrete. (10th September 2020) - Amer Algaifi, Hassan; Abu Bakar, Suhaimi; Rahman Mohd. Sam, Abdul; Ismail, Mohammad; Razin Zainal Abidin, Ahmad; Shahir, Shafinaz; Ali Hamood Altowayti, Wahid
Highlights: The bacterial growth was inhibited inside the concrete pore due to its high pH value of 13. The ureolysis was also decreased by up to 75% at pH value of 12–13. The ureolytic activity in the region close to the surface was better than that of the concrete pore. The healing ratio by microbial CaCO3 was limited in the deeper part of the crack zone. Abstract: Microbial calcium carbonate has been widely investigated to self-heal concrete cracks. However, the issue revolving around the efficacy of crack self-healing remains important. In particular, existing works are still lacking of a better understanding of the factors affecting the fundamental reactions involved as well as bacterial growth in harsh condition such as concrete. In this study, a comprehensive investigation was conducted to explore the bacterial growth and influential factors on the evolution of urea hydrolysis aimed to accurately promote calcium carbonate precipitation inside concrete. Sporosarcina pasteurii ATCC 11859 and native Lysinibacillus sphaericus strain Hass 1 were utilised to achieve the aim of this study. The ureolytic activity was investigated at pH values of 7–13 as well as different concentrations of urea, calcium nitrate tetrahydrate and bacterial cells. Additionally, the impact and extent of microbial activity on the compressive strength as well as self-healing of concrete cracks were also evaluated. The results indicated that the bacteria were able to survive in a dormant state without any reproduction at pH of 12–13. In addition, urea hydrolysis was essentially limited by pH, in which its efficiency decreased by up to 75% inside the concrete pore due to its high pH value of 13. Similarly, the favoured urea hydrolysis culture conditions were obtained as follows; pH of 9, concentration of calcium ions not exceeding 150 mM, urea concentration of 333 mM and optimum cells concentration of 2 × 10 8  cells/mL. Subsequent findings also revealed that the compressive strength of the concrete incorporated with spores, vegetative cells and urea-vegetative cells was improved by 9%, 10% and 15% compared to that of the control specimens respectively. Moreover, the complete healing of a 0.4 mm crack width was achieved after 70 d at the crack mouth, whereas the healing ratio was less than 15% at the deeper part of the concrete surface. As such, it could be concluded that concrete incorporated with the bacteria can be recognised as a future sustainable strategy for the purpose of self-healing of inevitable cracks to prolong concrete lifespan.